Bioabsorbable magnesium screw fixation for tibial tubercle osteotomy; a preliminary study - Ünal, Melih; Demirayak, Engin; Ertan, Mehmet Baris; Kilicaslan, Omer Faruk; Kose, Ozkan (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Metallic screws are commonly used to fix tibial tubercle osteotomies (TTO). However, hardware removal late after osteotomy union is one of the most common causes of reoperation following TTOs. The use of bioabsorbable screws may eliminate secondary surgeries, but there is no study on their use in this indication. The purpose of this retrospective study was to evaluate the safety and efficacy of bioabsorbable magnesium (Alloy: MgYREZr) screws in tibial tubercle osteotomy (TTO) fixation.Methods: Ten patients with objective patellar instability who underwent distal realignment procedure using Fulkerson TTO were retrospectively reviewed. The osteotomy was secured with two parallel 4.8 mm magnesium screws in all patients. Kujala score and Lysholm knee score were used to assess the functional outcomes before and after the operation. Union of the osteotomy, displacement, and other imaging findings were evaluated with serial knee radiographs during the follow-up.Results: There were five male and five female patients with a mean age of 23.4±9.2 years (range, 15-45). The mean follow-up duration was 11.5±3.2 months (range,6-17 months). The osteotomy united in all cases at an average of 3 months. No infection or wound healing problems were seen. A significant increase in Kujala (p:.005) and Lysholm knee scores (p:.005) were recorded in all patients.Conclusion: The findings support that bioabsorbable magnesium screws can be safely used as an alternative fixation technique in TTO. Furthermore, it provides the advantage to eliminate the need for implant removal.